2013
DOI: 10.1007/s11051-013-1778-z
|View full text |Cite
|
Sign up to set email alerts
|

Fast, microwave-assisted synthesis of monodisperse HfO2 nanoparticles

Abstract: A conventional solvothermal synthesis was compared to a microwave assisted method for the synthesis of HfO2 nanoparticles. In a microwave, the reaction could be completed in three hours, compared to three days in an autoclave. In the microwave synthesis the ensemble of particles was found to have a better size dispersion and a smaller average size (4 nm). The reaction mechanism was investigated and proof for an ether elimination process was provided. Post-synthetic modification with dopamine or dodecanoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…27 The reaction mixtures of the prop+EtOH, prop+H2O, ethoxide and acetate precursor are similar to the propoxide precursor, suggesting that only the ligand exchange and ether elimination takes place according to the first reaction scheme. The reaction mixture of the prop+TFA precursor on the other hand is similar to the chloride precursor, suggesting that also here the additional acid catalyzed condensation takes place (scheme 2).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…27 The reaction mixtures of the prop+EtOH, prop+H2O, ethoxide and acetate precursor are similar to the propoxide precursor, suggesting that only the ligand exchange and ether elimination takes place according to the first reaction scheme. The reaction mixture of the prop+TFA precursor on the other hand is similar to the chloride precursor, suggesting that also here the additional acid catalyzed condensation takes place (scheme 2).…”
Section: Resultsmentioning
confidence: 90%
“…We explored if a microwaveassisted solvothermal treatment for ZrO2 NCs results in NCs with identical properties in terms of diameter and crystallinity, yet at much shorter reaction times, since microwaves directly heat the precursor solution, resulting in faster and more homogenous heating. [26][27][28] In the original benzyl alcohol synthesis, zirconium propoxide was used as a precursor to synthesize cubic ZrO2 NCs. However, it has been shown before that the use of different precursor types can lead to different formation reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…10,49 Dodecanoic acid is dissociatively adsorbed on the HfO 2 NC surface ( Figure 1A), a binding motif classified as NC(X) 2 . 39 Since it was already shown that ligand exchange processes with carboxylic acids are governed by acidity 4,10,54,55 and that it proved possible to transfer NaYF 4…”
Section: Resultsmentioning
confidence: 99%
“…35 Our synthesis is facilitated by the presence of starting materials, such as the LiOH precursor, 36 that strongly couple with microwaves and with materials with high dielectric constants such as the HfO 2 that can effectively couple with microwave radiations at high temperatures, in a similar way to the ZrO 2 precursor. [37][38][39] Undoped Li 6 Hf 2 O 7 and doped compounds up to x = 0.05 were obtained as single phase samples at a temperature of 850…”
Section: Resultsmentioning
confidence: 99%